Determination of the constant Wo for local geoid of Vietnam and it’s systematic deviation from the global geoid - Truong, Nguyen Ngoc; Nhac, Tran Van (Vietnam Journal of Marine Science and Technology, 2017)
Constant Wo, defining the geoid, has important applications in the area of physical geodesy. With the development of artificial Earth satellite, constant Wo for the global geoid approximating the oceans on Earth can be calculated from an expansion of spherical harmonics - Stokes constants determined by observation of perturbations in artificial satellite’s orbits. However, the Stokes constants are limited, therefore the geoid constant Wo could not be calculated for local geoid (state geoid) from the mentioned expansion of spherical harmonics. In this paper, we present a method to determine the constant Wo for local geoid of Vietnam, using generalized Bruns formula and Neyman boundary problem. The initial data used are Faye gravity anomalies surveyed on land and sea of Southern Vietnam. The constant Wo is then used to calculate the systematic deviation of the local geoid of Vietnam from the global geoid EGM - 96